Comparison of manual toothbrushes with different bristle designs in terms of cleaning efficacy and plaque control: A pilot study - Habeeb Rahman (Wolters Kluwer Medknow Publications, 2023)
Objective: The aim of the study was to compare the cleaning efficacy and plaque control of the straight and angled bristle design manual toothbrushes. Materials and Methods: It was a pilot randomized trial comprising 30 dental students divided into 2 groups (group I flat bristle design toothbrush and group II zig-zag bristle design toothbrush) with 15 in each group. Prebrushing and postbrushing plaque scores were recorded at the baseline and at the end of 4 weeks using Turesky modification of Quigley and Hein plaque index. Results: Plaque and gingival scores were reduced significantly at 1 month in group II with P < 0.05 than compared to group I where P > 0.05. Mean GI and plaque scores of the criss-cross design were reduced significantly after 1 month (P < 0.05). Intergroup comparisons revealed that plaque and gingival scores significantly reduced (P < 0.05) at 1-month interval. Conclusion: Bristle design has significant impact on plaque removal capacity of a toothbrush. Toothbrush with zig-zag bristle design is efficient in removing plaque than the flat design of a toothbrush.